Controlling intracellular processing to enhance spherical nucleic acid immune stimulation - Janice Kang; Michelle H. Teplensky; Jasper W. Dittmar; Michael Evangelopoulos; Jeongmin Hwang; Chad A. Mirkin (Proceedings of the National Academy of Sciences, 2025)
To mount a robust and durable immune response, the antigen in a vaccine must be processed efficiently in the appropriate intracellular compartment. Here, we report an approach for optimizing the antigen processing pathway and efficiency by using the modular design of spherical nucleic acid (SNA) nanostructures. We utilized the substrate specificity of endoplasmic reticulum aminopeptidase1 (ERAP1), a protease known to generate major histocompatibility complex class I (MHC I) epitopes in the endoplasmic reticulum, to design two ERAP1-responsive peptide linkers (EPLs). The peptide linkers append the peptide antigen onto the SNAs to bias the processing pathway toward ERAP1 and to vary the antigen processing efficiency. The two EPLs varied ERAP1 antigen processing efficiency by 10-fold. Subsequently, the EPLs increased colocalization of the antigen with ERAP1 by up to ca. 58% when compared to an SNA that did not employ this linker. The EPL that drove more efficient cleavage, augmented antigen surface presentation by 30%, ex vivo CD8 + T cell proliferation by fivefold, and in vivo generation of proinflammatory and effector memory CD8 + T cells by 5% and 18%, respectively. Furthermore, the more efficiently processed EPL-containing SNA resulted in a 2.5-fold more effective inhibition of E.G7-OVA lymphoma tumors in vivo. Taken together, these findings underscore the importance of the deliberate and rational design of vaccine structures to spatially bias antigen processing and elevate its processing efficiency to augment immune stimulation.